The economic impact of climate change on road infrastructure in sub-Saharan Africa countries: Evidence from Ghana - Daniel Kwabena Twerefou; Kwame Adjei-Mantey; Niko Lazar Strzepek (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Climate change scenarios for many Sub-Saharan African countries including Ghana indicate that temperatures will increase while rainfall will either increase or decrease. The potential impact of climate change on economic systems is well-known. However, little has been done to assess its economic impact on road infrastructure. This work assesses the economic impact of climate change on road infrastructure using the stressor-response methodology. Our analysis indicates that it will cumulatively (2020-2100) cost Ghana US473 million to maintain and repair damages caused to existing roads as a result of climate change (no adapt scenario). However, if the country adapts the designing and construction of new road infrastructure expected to occur over the asset's lifespan (adapt scenario), the total cumulative cost will increase to US678.47 million. The paper also provides decadal and average annual costs up to the year 2100 for the ten regions through the potential impacts of 54 distinct potential climate scenarios.
Keywords: Q51; Q55; 330; climate change; impacts assessment; road infrastructure; stressor response